Practical recommendations for screening of information on the drug safety - E. Yu. Pasternak; T. M. Bukatina; R. N. Alyautdin; B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Active development of pharmacology in recent decades and the potential emergence of a large number of new drugs not only expanded the possibilities of treatment, but also increased the risk of adverse effects. That is the risk of severe, often irreversible complications due to drug therapy are attracted to the problem of drug safety the attention of practitioners and other health professionals. This article presents practical recommendations on possible sources for screening of information on the drug safety, which can operate in their activity as health professionals.